Atmega328P-based X-ray Machine Exposure Time Measurement Device with an Android Interface - Sigit Widadi; Muhammad Khairul Huda; Irfan Ahmad; Omar tanane (Universitas Muhammadiyah Yogyakarta, 2020)
The purpose of this study was to design an X-ray microcontroller-based ATmega328P microcontroller exposure time measurement device. That can be done by integrating an X-ray detection circuit, analog signal conditioner, ATmega328P microcontroller and Bluetooth module HC-05 to display and control the measurement results on mobile phones Android. The benefits of this research are expected to be able to increase knowledge and expertise in the field of radiology instruments through X-ray machine parameter measurement techniques and assist technicians to calibrate the X-ray exposure time parameters.